SHARIA ECONOMIC BUSINESS ETHICS IN FACING THE ERA OF ECONOMIC DIGITALIZATION IN THE FUTURE - Barnamij, Najhah; Salsabila, Syafira; Sohibul Migfar, Muhammad; Rohmat, Saepur; Ridwan, Mohammad; Murtadho, Ali (Penerbit Lafadz Jaya, 2022)
Islam places ethics and morals in the most important position in life. Islamic economic business ethics is here to be a solution for self-development in the world of business and actions that are in accordance with norms and religion. The research used is qualitative research, with data collection techniques such as tracking journals, books and articles that discuss Islamic economic business ethics. After the data sources have been collected, the author will analyze them and then draw conclusions because of the research. The aim of this research is to explore how big the opportunities for doing business in the era of digitalization are while still prioritizing morals. This research reveals Islamic economic business ethics in facing future economic challenges, namely by continuing to keep up with the times and innovating and cultivating one's own abilities to be able to adapt to increasingly advanced and developing conditions, the business world aims to produce much better economic growth and continue to prioritize ethics and morals.